Analisis Spasial: Prevalensi Hipertensi Dengan PHBS dan Jumlah Posbindu Kabupaten Tasikmalaya Tahun 2023 - Dadan Yogaswara; Yuni Laferani; Irfan Nafis Sjamsuddin; Wulan Tri Yutanti; Kharisma Nurul Fazrianti Rusman; Meita Tyas Nugrahaeni (KOLONI, 2026)
The increasing prevalence of hypertension has become a major health problem, both globally, regionally, and nationally. In Indonesia, according to the 2023 Indonesian Health Survey (SKI), the prevalence of hypertension was recorded at 30.8%, and in West Java at 34.4%. According to the 2023 health profile data from Tasikmalaya Regency, 76.8% of hypertension sufferers received healthcare services. Understanding the detrimental patterns of hypertension requires government and community efforts to implement early prevention. Data on hypertension incidence can be mapped using a Geographical Information System (GIS). This study aims to examine spatial effects in Tasikmalaya Regency, West Java. This study uses ecological study used aggregate data. The data source was the 2023 health profile of Tasikmalaya Regency. All sub-districts were used as units of analysis. Data analysis was performed using the GeoDa application. Results Shows a negative spatial autocorrelation between hypertension and the number of Posbindu (Moran's I: -0.817; p-value: 0.01) and Healthy Lifestyle Behavior (Moran's I: -0.152; p-value: 0.04). Conclusion: This study demonstrates a negative spatial autocorrelation between hypertension and Healthy Lifestyle Behavior and the number of Posbindu (Integrated Health Posts). Interventions to improve Healthy Lifestyle Behavior and equalize the number of Posbindu are needed, particularly in areas with high hypertension cases that are adjacent to areas with low Healthy Lifestyle Behavior.